ChemInform Abstract: A Versatile Route to Benzodiazocine and Spiropyran Derivatives Through Chalcones. Issue 44 (14th October 2013) - George, Johnson; Singh, Saurabh; Joshi, Rahul; Pardasani, Ramchand T.
Abstract Various new benzodiazocine derivatives (V) are obtained by cyclocondensation of benzothiophenes (III) with o‐phenylene diamine.